Diverse Distribution and Gene Expression on the 21-Gene Recurrence Assay in Breast Cancer Patients with Locoregional Recurrence Versus Distant Metastasis - Lu Y; Tong Y; Huang J; Lin L; Wu J; Fei X; Chen X; Shen K (Cancer Management and Research, 2021)
Yujie Lu,1,* Yiwei Tong,1,* Jiahui Huang,1 Lin Lin,2 Jiayi Wu,1 Xiaochun Fei,3 Xiaosong Chen,1 Kunwei Shen1 1Department of General Surgery, Comprehensive Breast Health Center, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China; 2Department of Clinical Laboratory, Ruijin Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, 200025, People’s Republic of China; 3Department of Pathology, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaosong Chen; Kunwei ShenDepartment of General Surgery, Comprehensive Breast Health Center, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of ChinaEmail chenxiaosong0156@hotmail.com; kwshen@medmail.com.cnBackground: It remains uncertain whether the 21-gene recurrence score (RS) of a primary tumor has selective prognostic value for locoregional recurrence (LRR) or distant metastasis (DM). The current study aimed to compare the distribution and single-gene expression on the RS panel in breast cancer patients with LRR versus DM.Methods: Consecutive early breast cancer patients who had been operated on at the Comprehensive Breast Health Center, Ruijin Hospital from January 2009 to December 2016 were retrospectively reviewed. Patients were divided into LRR, DM, and no-recurrence groups according to the first reported recurrent event. Comparison and subgroup analysis of 21-gene RS, RS category, and single-gene expression on the RS panel were conducted among patients with different recurrence status.Results: A total of 1,287 patients were included, with median follow-up of 61.5 months, and 27, 47, and 1,213 patients were classified as LRR, DM, and no recurrence groups, respectively. RS was significantly diversely distributed among the three groups (P< 0.001). No-recurrence patients (median 22) presented much lower RS than LRR (median 39, P< 0.001) and DM (median 30, P< 0.001) patients. LRR patients had lower PR (P< 0.001), BCL2 (P=0.010), and CEGP1 (P< 0.001) expression, and DM patients had higher STMY3 (P=0.019) expression than no-recurrence patients. Moreover, CEGP1 expression was significantly lower in the LRR group than the DM one (P=0.028).Conclusion: RS was differently distributed between recurrent and nonrecurrent patients. PR, BCL2, CEGP1, and STMY 3 expression was associated with LRR and DM, while CEGP1 was lower in the LRR group than DM patients, warranting further clinical evaluation.Keywords: breast cancer, 21-gene recurrence assay, gene expression, locoregional recurrence, distant metastasis